Toxicity of copper nanopartical in Daphnia magna - Kien, Nguyen Trung; Thu Huong, Tran Thi; Thuy, Duong Thi (Academia Journal of Biology, 2017)
Nanotechnology has been widely and efficiently used in many areas due to unique physicochemical properties of nano-materials in comparison with their larger bulk counterparts. However, materials application process also have potential risks to human health and the ecological environment. To evaluate the safety of nanomaterials in water environment, the experiments on aquatic organisms should be carried out to test the toxicological effects of nanomaterials. A crustacean organism, Daphnia magna, has been used as a model organism for testing the toxicity in the aquatic environment because of unique features such as easy to identify and easy to control with toxic substances, widely distributed, reproduce quickly in the form of virgin production in a short time. The aims of this study is to evaluate the toxicity of copper nanomaterials (Cu) on the growth of D. magna. The material concentration selected to test toxicity ranged from 0 (control) to 5 ppm. After 24 h and 48 h of exposure, the highest survival rate of the D. magna 100% was found at a concentration of 0.01 ppm, whereas the copper nanomaterial concentrations of 1, 3 and 5 ppm caused 100% growth inhibition of D. magna. The acute toxicity (LC50) of Cu nanoparticle to D. magna after exposure for 24 and 48h were 0.289 ppm and 0.1 ppm, respectively. Citation: Nguyen Trung Kien, Tran Thi Thu Huong, Duong Thi Thuy, 2017. Toxicity of copper nanopartical in Daphnia magna. Tap chi Sinh hoc, 39(2): 258-264. DOI: 10.15625/0866-7160/v39n2.9089 *Corresponding author: nguyenkien.et@gmail.com Received 29 December 2016, accepted 20 March 2017